ANALISIS DAMPAK REGULASI TERHADAP SISTEM GANJIL-GENAP DALAM MENGATASI KEMACETAN DI PROVINSI DKI JAKARTA - Salsabila Veliana Zahrah; Lina Aryani; Mochamad Faizal Rizky (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
social and political studies; however, there is still limited evidence regarding the impact of motor vehicle restrictions in urban areas. This study aims to analyze the impact of the odd-even traffic policy in addressing traffic congestion in DKI Jakarta Province. A qualitative method with a case study approach was used, involving data collection through interviews, field observations, policy document analysis, and media articles. The data were analyzed using the pattern matching technique. The results show that the odd-even policy is fairly effective in reducing traffic congestion, supported by inter-agency coordination, officer training, and routine evaluations. Nonetheless, challenges remain, including uneven infrastructure, limited personnel, public violations, and suboptimal community participation. This research is expected to provide input for the government to improve the implementation quality of the odd-even policy in the future. This case study also offers new insights into urban traffic policy, particularly in the formulation and evaluation of transportation regulations in large cities.